How does narcissism influence corruption? The moderating role of boredom. (December 2021) - Gu, Zibei; He, Yuyang; Liu, Li; Liang, Yuan; Huang, Lingling; Dang, Jianning; Wei, Cong; Liu, Zhen; Su, Qian
Abstract: Previous research has suggested that narcissism can effectively induce corruption; however, those studies were unable to predict what triggered narcissists to engage in corruption. Our research extends this line of research by showing the moderated model that narcissism was positively associated with corruption only under conditions of boredom. In Study 1, we preliminarily confirmed our moderated model using a correlational design. In Studies 2 and 3, we manipulated boredom using different paradigms to explore the relationship between narcissism and corrupt intent (Study 2) and behavior (Study 3). The results of all three studies consistently indicated that narcissism positively predicted corruption when boredom was high, whereas the effect disappeared when boredom was low. Our results illustrate the importance of reducing boredom to inhibit the corruption of narcissists. Highlights: Boredom moderates the relationship between narcissism and corruption. When boredom is high, narcissism positively predicts corruption. When boredom is low, the relationship between narcissism and corruption disappears.